Biochemical and Neurobehavioral Changes in the Rat Model of Parkinson’s Disease with Suprathreshold Exercise and Usnic Acid: Life Sciences-Neurosciences - Sanil Kumar, Devika; Sivanesan, Senthilkumar; Vasudevan Nair, Lal Devayani; Vijayaraghavan, Rajagopalan (International Journal of Life Science and Pharma Research, 2023)
Finding a solution for Parkinson's disease has been a challenge to researchers despite advances in medicinal research. None of the options available so far has been able to reverse dopaminergic damage or increase endogenous dopamine production from existing dopaminergic cells in Parkinson's disease. Research in Parkinson’s disease has not so far resulted in finding better solutions for reversing dopaminergic damage or increasing dopamine production. Above-the-threshold (suprathreshold) exercises producing improvement have been documented with supporting clinical and imaging findings but without any biochemical evidence. Above-the-threshold (suprathreshold) exercises producing improvement in Parkinson's disease have been documented with supporting clinical and imaging findings. To the best of our knowledge, the biochemical basis of this improvement has not been studied in detail. Recently, biomolecules like usnic acid have been shown to improve dopamine levels through protective and regenerative effects. This study aimed at understanding the biochemical basis of the improvement following suprathreshold exercises and usnic acid. The objectives were to assess whether the suprathreshold exercise produces improvement in PD rat models and, if so, to understand the biochemical basis of improvement and compare the mechanism with that of usnic acid.The effect of suprathreshold exercise and usnic acid on Parkinson’s disease Hence, this study was conceived to understand whether the exercise produces results due to a similar mechanism that had never been reported before. Parkinson's disease was compared with rotenone alone, rotenone and high-fat diet models, and control. Induced with rotenone and a high-fat diet, the effect of suprathreshold exercise was compared to that of usnic acid, the rotenone alone model, and control. Locomotor behaviour was assessed with an actophotometer and rotarod. Western blotting assessed the blood biochemical parameters, antioxidant and dopamine levels in addition to α-synuclein, tyrosine hydroxylase, Nurr1, and HSP70 levels. Usnic acid decreased oxidative stress markers like MDA, peroxynitrite and nitric oxide, indicating lesser oxidative stress, increased dopamine and serotonin levels and decreased α-synuclein expression. But the suprathreshold exercise did not significantly affect oxidative stress markers nor increased dopamine levels. However, α-synuclein expression was decreased. Compared with usnic acid, lower Nurr1 levels in the suprathreshold group demonstrate lesser protective and regenerative effects on dopaminergic neurons. HSP70 levels indicate that improvement in suprathreshold exercise resulted from preventing misfolding of α-synuclein or through a noncanonical interaction, and comparable locomotor behaviour was observed in both groups. Biomolecules like brain-derived neurotropic factors produced by suprathreshold exercises acting centrally and in muscles might have also contributed to improvement in this group. When usnic acid increased dopamine levels in the brain through protective effects on dopaminergic neurons, antioxidant effects, and reduced expression of α-synuclein, suprathreshold exercise did not increase dopamine, decreased α-synuclein and had less antioxidant effects. This study biochemically proves that suprathreshold exercise alleviates Parkinson’s disease symptoms by preventing α-synuclein misfolding and not by mechanisms other than increasing dopamine, neuroprotection or regeneration of dopaminergic neurons, which require further studies in humans.